SALAT DUHA SEBAGAI BUDAYA POPULER DALAM PEMAKNAAN ANGGOTA MAJELIS DHUHA BANTUL - Afifah, Nurul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
Majelis Duha Bantul is a community that consistly performs Duha prayer in specific and unique style; by performing it collectively, in certainly days, etc. The major question in this research is how they interpretate the duha prayer that they commit? This research is field research with the descriptive, qualitative and analitic genre by applying etnographical approach and the sociology of knowledge theory, and applying the interview and observation as the method. This result of this research reveal three meaning of the duha ritual in the perspective of majelis duha Bantul: (1) objective meaning that is the meaning of the Duha Prayer which majelis duha Bantul understood from the hadis that suggesting the duha prayer. (2) expressive meaning which personally diverse, several person interpretate duha prayer as the effort to attain the physical and mental health, some men religiously interpretate that duha prayer is one of many ways to reach the wordliness success and the hereafter happiness, etc. (3) documenter meaning that show the duha prayer as the ritual based on the hadis advice but in very fact this ritual is disputed still by some scholars; by commiting the duha prayer it means they indentified them self as the community that appraise the duha prayer collectively is the sunah ritual. And finally this duha ritual subconsciously become the living hadis ritual it self.